Introducing the Ethnobotany of Indonesian Medicinal Plants and Jamu to the International Community - Setiadi, Anandita Eka; Kurniasih, Dedeh; Ibrahim, Khairunnisa; Lostari, Linda; Nini, Diana; Yuninur, Lilik (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The use of medicinal plants and traditional herbal medicine reflects the local wisdom of the Indonesian people, deeply rooted in their culture and daily life. However, international awareness and appreciation of this heritage remain limited. To address this, a community engagement program was implemented to promote Indonesian medicinal plants and jamu to a broader audience. The program aimed to enhance cross-cultural knowledge exchange and foster research collaboration. This initiative involved a series of workshops introducing various medicinal plants and practical demonstrations on preparing jamu. The activities were conducted at the JAKIM office, Sarawak, Malaysia, with 42 participants in attendance. Data were collected through participant feedback surveys, assessing aspects such as the clarity of instruction, effectiveness of workshop methods, practical relevance, and overall benefits. The results indicated overwhelmingly positive responses, with participants expressing appreciation for the informative content and hands-on approach. The findings suggest that such programs play a crucial role in increasing awareness and preserving traditional knowledge. In conclusion, this initiative successfully supported knowledge and cultural exchange while fostering continued research collaboration in the field of medicinal plants and herbal medicine.